Analysis of Factors Related to the Compliance of Nurses in Applying the Standard of Nursing Care Inpatient at the Bakti Mulia Hospital Muncar Banyuwangi - Lujeng Galih Pradana (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Nurses are an important and strategic component in the implementation of health services. In performing its duties, a nurse is required to understand the process and standards of nursing practice consisting of the stage of assessment, problem identification (nursing diagnosis), planning, implementation, and evaluation. The purpose of this research is to know the factors related to the compliance of the nurses in applying the standard of nursing care of inpatient at Bakti Mulia Hospital Muncar Banyuwangi. The research design used was cross sectional. The study population was all nurses in the hospital ward of Bakti Mulia Hospital Muncar as many as 48 people and a large sample 48 people. The sampling technique uses saturated sampling. Data collection using questioner then analyzed using logistic regression. The results showed that there was no effect of long time to work on nurse compliance in the application of nursing care standard (p = 0,425; OR = 0,495), no influence of education to nurse compliance in applying nursing care standard (p = 0,151; OR = 2,189) the effect of motivation on nurse compliance in applying nursing care standard (p = 0,008; OR = 0,084). While the most dominant factors that influence the compliance of nurses in the application of nursing care standards in Bakti Mulia Hospital Muncar Banyuwangi regency (p = 0.011; OR = 0.7200). Based on the research, it is necessary to improve the ability (knowledge and skills) to apply nursing care following the workshop of applying the nursing care so that the responsibility for the task can be improved.